Accuracy of intraoperative aberrometry versus preoperative biometry for intraocular lens power selection in short and long eyes - Tañá-Rivero, Pedro; Orts-Vila, Paz; Tañá-Sanz, Pedro; Tañá-Sanz, Santiago; Ruiz-Mesa, Ramón; Montés-Micó, Robert (Frontiers in Medicine, 2024)
To compare the accuracy of intraoperative wavefront aberrometry using the ORA VLynk system with different biometry-based formulas in short and long eyes after cataract surgery. METHODS: This prospective study considered 48 eyes with axial lengths of <22.1 mm and 48 eyes with axial lengths of >25.0 mm. All eyes were implanted with the monofocal AcrySof IQ IOL, the power being determined using the ORA VLynk. The postoperative spherical equivalent (SE) at 3 months was compared to that predicted preoperatively using the SRK/T, Hoffer Q, Haigis, Holladay 2, Barrett Universal II, and Barrett True K formulas and intraoperatively using the ORA VLynk. Mean numerical and absolute errors and the percentage of eyes within ±0.50 D/1.00 D of their target were obtained. RESULTS: For long eyes, the mean absolute error values were 0.35, 0.52, 0.34, 0.30, 0.29, 0.27, and 0.24D for SRK/T, Hoffer Q, Haigis, Holladay 2, Barrett Universal II, Barrett True K, and ORA VLynk, respectively (p<0.001). These values were 0.55, 0.45, 0.49, 0.40, 0.44, 0.44 and 0.50 D for short eyes, respectively (p<0.001). The proportions of long eyes within ±0.50 D of the target were 77.